Inhibitory test of andaliman (Zanthoxylum achantopodium DC) extract mouthwash against dental plaque bacteria - Martina Amalia; Priscillia Sekar Yosuana; Iqlima Salsabila binti Mohammad; Filya Suri Risky Nababan; Zulkarnain; Pitu Wulandari; Aini Hariyani Nasution; Armia Syahputra (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Andaliman (Zanthoxylum achantopodium DC) is an endemic plant that is found in the province of Sumatera Utara, Indonesia. It contains secondary metabolites, such as alkaloids, flavonoids, glycosides, saponins, tannins, and triterpenoids/steroids, which can potentially be used as a mouthwash. Streptococcus sanguinis and Staphylococcus aureus are the primary colonizing bacteria in plaque formation. Bacterial plaque is known to be the main cause of periodontal disease but can be controlled mechanically and chemically using mouthwash. Purpose: To determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of andaliman extract mouthwash (2%, 4%, 8%) against Streptococcus sanguinis ATCC®10556™ and Staphylococcus aureus ATCC® 25923™. Methods: This is a laboratory study with a post-test control-only design. The sample consists of andaliman extract mouthwash (2%, 4%, 8%), a positive control (chlorhexidine gluconate 0.2%), and a negative control (mouthwash formulation without andaliman extract) with three repetitions for each group. Data were analyzed with the one-way ANOVA test and post hoc LSD test. Results: The andaliman extract mouthwash with concentrations of 2%, 4%, and 8% significantly reduced the number of Streptococcus sanguinis and Staphylococcus aureus colonies (p<0.05), and there was a significant difference in the andaliman extract mouthwash with concentrations of 2%, 4%, and 8% compared to the negative control. Conclusion: Andaliman extract mouthwash with a concentration of 8% was more effective in inhibiting Streptococcus sanguinis growth than Staphylococcus aureus. The MIC values for both bacteria were 2%, but the study could not determine the MBC value.